2016
DOI: 10.1089/jmf.2016.3767
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Proteasome Inhibition by Alkaloid Extract fromMurraya koenigiiLeaves in Breast Cancer Cells—Molecular Docking Studies

Abstract: Murraya koenigii (curry tree) leaves are rich in bioactive compounds such as flavonoids, alkaloids, and coumarins. Alkaloids from M. koenigii leaves have antianalgesic, antiulcerogenic, antiobesity, and antitumor activities. In this study, we tested the cytotoxic and proteasome-inhibitory potential of a total alkaloid extract (TAE) from M. koenigii leaves in the breast cancer cell line MDA-MB-231. The TAE decreased cell viability with an IC of 14.4 μg/mL and altered growth kinetics of breast cancer cells. TAE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A methanolic extract of M. koenigii was reported to have the ability to reduce proliferation in breast cancer cell lines [116]. The total alkaloid extracted from M. koenigii leaves has been shown to have promising cytotoxic activity in breast cancer cells, with an IC 50 of 14.4 µg/mL [117]. The anticancer activity of mahanine and isomahanine in human oral squamous cell carcinoma CLS-354 has also been reported [96].…”
Section: Anticancer Activity (In Vivo and In Vitro)mentioning
confidence: 97%
“…A methanolic extract of M. koenigii was reported to have the ability to reduce proliferation in breast cancer cell lines [116]. The total alkaloid extracted from M. koenigii leaves has been shown to have promising cytotoxic activity in breast cancer cells, with an IC 50 of 14.4 µg/mL [117]. The anticancer activity of mahanine and isomahanine in human oral squamous cell carcinoma CLS-354 has also been reported [96].…”
Section: Anticancer Activity (In Vivo and In Vitro)mentioning
confidence: 97%
“…Caspases-3 activity and TUNEL-positive cells enhanced after treatment with M. koenigii extract, indicating accelerated apoptosis (Noolu et al 2016). Total alkaloid extract from M. koenigii reduced breast cancer cell viability (IC50 = 14.4 g/mL), altered development dynamics, arrested cells in the "S" stage, and induced cell death (MDA-MB-231) (Ismail et al 2016). MTT assay showed the antitumor effectiveness of M. koenigii silver nanoparticles against breast cancer cell types (MDAMB-231).…”
Section: Murraya Koenigiimentioning
confidence: 99%
“…An experimental study reported the cytotoxic activities of alkaloid extract from M. koenigii in the breast cancer cell line MDA-MB-231 with an IC 50 of 14.4 μ g/mL [ 59 ]. Mahanine, a carbazole alkaloid isolated from M. koenigii and M. minutum, and its analogs have shown significant cytotoxic and anticancer activities in prostate cancer studies.…”
Section: Beneficial Pharmacological Activities Of M Koenigii M Minutum and C Indica mentioning
confidence: 99%